Technology of integration of physical culture and sports activities and patriotic education of students - Stetsenko N.V. ,; Fayzrakhmanov I.I. , (Theory and Practice of Physical Culture, 2023)
As part of the survey, experts (n-38) expressed the opinion that the integration of sports and patriotic education of students is an important element of their education and civic and personal formation (89.4%). During the implementation period, the participants of the Program improved their psychophysical preparedness (78.9%), moral qualities (92%), increased self-esteem (97.4%) and strengthened patriotic feelings (81.6%). These results confirm the importance of the task of forming civic identity and patriotism among students of physical education and sports universities, which has acquired special importance in the context of international sports isolation.